BCR-ABL1 Doubling-Times and Halving-Times May Predict CML Response to Tyrosine Kinase Inhibitors - Pennisi, Maria Stella; Stella, Stefania; Vitale, Silvia Rita; Puma, Adriana; Di Gregorio, Sandra; Romano, Chiara; Tirrò, Elena; Massimino, Michele; Antolino, Agostino; Siragusa, Sergio; Mannina, Donato; Impera, Stefana; et al. (Frontiers in Oncology, 2019)
In Chronic Myeloid Leukemia (CML) successful treatment requires accurate molecular monitoring to evaluate disease response and provide timely interventions for patients failing to achieve the desired outcomes. We wanted to determine whether measuring BCR-ABL1 mRNA doubling-times (DTs) could distinguish inconsequential rises in the oncogene’s expression from resistance to tyrosine kinase inhibitors (TKIs). Thus, we retrospectively examined BCR-ABL1 evolution in 305 chronic-phase CML patients receiving imatinib mesylate (IM) as first line treatment. Patients were subdivided in two groups: those with a confirmed rise in BCR-ABL1 transcripts without MR3.0 loss and those failing IM. We found that the DTs of the former patients were significantly longer than those of patients developing IM resistance (57.80 vs 41.45 days, p=0.0114). Interestingly, the DT values of individuals failing second-generation (2G) TKIs after developing IM resistance were significantly shorter than those observed at the time of IM failure (27.20 vs 41.45 days; p=0.0035). We next wanted to establish if decreases in BCR-ABL1 transcripts would identify subjects likely to obtain deep molecular responses. We therefore analyzed the BCR-ABL1 halving-times (HTs) of a different cohort comprising 174 individuals receiving IM in first line and observed that, regardless of the time point selected for our analyses (6, 12 or 18 months), HTs were significantly shorter in subjects achieving superior molecular responses (p=0.002 at 6 months; p<0.001 at 12 months; p=0.0099 at 18 months). Moreover, 50 patients receiving 2G TKIs as first line therapy and obtaining an MR3.0 (after 6 months; p=0.003) or an MR4.0 (after 12 months; p=0.019) displayed significantly shorter HTs than individuals lacking these molecular responses. Our findings suggest that BCR-ABL1 DTs and HTs are reliable tools to identify, respectively, subjects in MR3 that are failing their assigned TKI or to recognize patients likely to achieve deep molecular responses that should be considered for treatment discontinuation.